Math, asked by kaaraksh, 1 year ago

Solve using Law of exponents:

Attachments:

Answers

Answered by raj3294
0

Answer:

Step-by-step explanation:

(1) 2^2/3* 2^1/3                            [A^M*A^N=A^(M+N)]

  = 2^(2/3+1/3)

  = 2

(2) (3^1/5)^4

   = 3^5/4                                      [(A^M)^N = A^MN]

(3)(7^1/5)/(7^1/3)                             [ A^M/A^N=A^M-N]

= 7^(1/5-1/3)

= 7^(-2/15)

(4) 13^(1/5) * 17^(1/5)                        [ A^M*B^M=( A*B)^M]

= (13*17)^(1/5)

= 221^(1/5)

(5)2 ^(2/3+1/5)                                [SAME AS 1]

= 2^(7/15)

(6) (1/3^3)^7

= (1/3)^21                                            [ SAME A S 2]

(7)11^(1/2)/11^(1/4)

= 11^(1/2-1/4)

=11^(1/4)                                                [ SAME  AS 3]

(8) 7^(1/2)*98^(1/2)                         [ SAME AS 4].

= (7*8)^(1/2)

= 56^(1/2).

HOPE THIS HELPS.

Similar questions